Nicholas of Cusa’s Cribratio Alkorani (1461): Sources, Scholars, and Narrative Maintenance - Nathan Ron (Wrocławski Przegląd Teologiczny)
The article points out that Cusanus scholars tend to celebrate their subject as a proponent of ‘interreligious dialogue.’ Preoccupied with Cusanus’ irenic and much-praised dialogue On the Peace of the Faith (De Pace Fidei, 1453), they either ignore or belittle significant issues, such as Cusanus’ active engagement in preparations for a crusade, the harsh polemical Scrutiny of the Qur’an (Cribratio Alkorani, 1461), which rejects the prophethood of Mohammad, and the harsh expressions against Mohammad in Cusanus’ sermons. The author’s thesis is that scholars employ filters that establish their agenda by devaluing or wiping away entirely anything not in line with On the Peace of the Faith; they defend and cultivate the prevalent narrative and their hero’s received image. In this paper, Nathan Ron exposes this unacceptable phenomenon and condemns it.